Relationship between Persistent Processus Vaginalis and Cryptorchidism-A Study in the Eastern Region of India - Asis Kumar Ghosal; Biswanath Mukhopadhyay; Anirban Sadhu (Al Ameen Medical College, 2011)
Cryptorchidism is typically associated with an ipsilateral inguinal hernia and is at a greater risk for trauma. Premature infants also have a higher incidence of cryptorchidism. In the present study conducted at the Paediatric Surgery department of a teaching hospital in Kolkata 25 male patients in the paediatric age group with cryptorchidism were studied for the occurrence of persistent processus vaginalis. Necessary investigations were done and these were corroborated with the surgical findings. The findings were recorded in tabular form and the relevant results were compared with similar studies done elsewhere. Patients with history of premature birth were not included in the study. Early detection of this condition is of utmost importance to prevent future complications.